Keanekaragaman Makrozoobenthos pada Hutan Mangrove yang Direhabilitasi di Pantai Timur Sumatera Utara - ', Onrizal; Simarmata, Fernades SP; Wahyuningsih, Hesti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
Macrozoobenthos is a group of important fauna in mangrove ecosystem. Mangrove rehabilitation is required toincrease biodiversity and density of fauna, including macrozoobenthos. The aim of this research was to studyinfluence of biotic and abiotic factors to diversity and abundance of macrozoobenthos. The research was conductedat natural and rehabilitated mangrove forest in Percut Sei Tuan, east coastal of North Sumatra. The results showedthat density of macrozoobenthos were significantly correlated to the soil texture, soil organic carbon and pH.Besides, macrozoobenthos diversity was mostly influenced by stand basal area, salinity and silt proportion of soiltexture.